2002
DOI: 10.1042/cs20010281
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular disease is associated with abnormal arteriolar diameter relationships at bifurcations in the human retina

Abstract: A B S T R A C TArterial diameters at branch points are believed to conform to design principles that optimize circulatory efficiency and maintain constant shear stress across arterial networks. The objective of this study was to examine whether optimality at bifurcations is affected in individuals with atherosclerosis. Retinal images were analysed in normotensive men with abnormal ankle brachial index (n l 13) and healthy controls (n l 8), matched for age and clinic blood pressure. Compared with controls, men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…We found no associations with branching angles (the association with PVD is based on few patients), consistent with some previous studies finding no link between angles and hypertension (31), peripheral vascular disease (15) and death with IHD and stroke (16). It is possible that angles may not predispose to or change in response to systemic disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no associations with branching angles (the association with PVD is based on few patients), consistent with some previous studies finding no link between angles and hypertension (31), peripheral vascular disease (15) and death with IHD and stroke (16). It is possible that angles may not predispose to or change in response to systemic disease.…”
Section: Discussionsupporting
confidence: 92%
“…An increased branching coefficient represents wider daughter vessels and a decreased branching coefficient indicates narrower daughters compared with the parent vessel; each may affect the energy required to deliver blood around the body and hence the efficiency of the circulatory system. Some studies suggest that this theory may be biologically true, for example abnormalities in branching coefficient have been associated with cognitive impairment (14), peripheral vascular disease (15) and ischaemic heart disease (IHD) (16).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] More recently, new computer-based programs have been developed to perform quantitative assessments of geometric parameters of the retinal vasculature, such as retinal vascular tortuosity and branching angles. [12][13][14][15][16][17] The vascular network is believed to be organized to minimize shear stresses and work across the system, 18 -21 and these parameters may provide an indication of how closely a given network conforms to the geometrical ideal. In contrast with retinal vessel caliber measurements, which are generally performed at a fixed location relative to the optic disc and which measure only a single property of the retinal vessels, geometric network measures provide a better indication of the overall health of the vascular system.…”
mentioning
confidence: 99%
“…In contrast with retinal vessel caliber measurements, which are generally performed at a fixed location relative to the optic disc and which measure only a single property of the retinal vessels, geometric network measures provide a better indication of the overall health of the vascular system. For example, Chapman et al 16 have demonstrated that retinal vascular diameters at bifurcation points deviated significantly from the optimal in subjects with peripheral vascular disease but conformed to optimal values in healthy controls. Low-birth-weight men have also been shown to have narrower bifurcation angles, 22 suggesting a mechanistic link between impaired fetal development and the subsequent development of cardiovascular diseases like hypertension.…”
mentioning
confidence: 99%
“…In an ideal configuration, the bifurcation of arteries will have an optimal branching arrangement to facilitate effective blood flow6. Some studies have shown that the bifurcation angle is narrowed in subjects with hypertension7 or with low birth weight8, but not in subjects suffering from a peripheral vascular disease with abnormally low ankle/brachial indices9.…”
Section: Introductionmentioning
confidence: 99%